The The influence of competence, independence, and professionalism of government internal auditors on audit quality at the representative offices of the financial and development supervisory agency (BPKP) - Nadhifa, Nisrinatul; Haliah, Haliah; Nirwana, Nirwana (Journal of Multidisciplinary Academic Business Studies, 2024)
Purpose: This study aims to determine The Influence of Competence, Independence, and Professionalism of Government Internal Auditors on Audit Quality at the Representative Offices of the Financial and Development Supervisory Agency (BPKP) of South Sulawesi Province. Research methodology: A quantitative approach was employed using questionnaires distributed to internal auditors. From a population of 143 auditors, 40 respondents were selected. Data were analyzed using descriptive statistics, classical assumption tests, multiple regression analysis, t-tests, and F-tests. Results: The findings show that competence and professionalism have positive and significant effects on audit quality, while independence has a positive but insignificant effect on audit quality. Competence, independence, and professionalism collectively have a significant impact on audit quality. Conclusions: Audit quality is strongly influenced by the competence and professionalism of internal auditors, while independence contributes positively but not significantly. Ensuring high competence and professionalism enhances the credibility and reliability of government audit. Limitations: The study was limited to one BPKP representative office with a relatively small sample size, which may restrict the generalizability of the findings to other BPKP offices. Contribution: This research provides empirical evidence for improving audit quality by strengthening the competence and professionalism of internal auditors, offering valuable insights for audit institutions and policymakers to enhance government accountability.